2014
DOI: 10.4238/2014.april.16.1
|View full text |Cite
|
Sign up to set email alerts
|

Role of inflammatory parameters in the susceptibility of cerebral thrombosis

Abstract: ABSTRACT. We aimed to investigate the association of inflammationrelated genes such as IL-10, IL-6 and IL-1B with risk of ischemic stroke. We included 426 cases with ischemic stroke and 426 health controls from Xinxiang, China. Genomic DNA was extracted from the buffy coat layer of collected blood with the TIANamp blood DNA kit. Diabetes, hypertension, obesity, and smoking habits were associated with risk of ischemic stroke. We found that individuals carrying the CC genotype of IL-1B rs1864169 had a higher ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…These 3 polymorphisms were found to occur in frequencies consistent with HWE in the control populations of the vast majority of the published studies. There were 10 studies based on Asian population, 4 , 13 , 16 , 17 , 20 , 23 , 25 , 28 , 32 , 48 16 studies conducted in white population, 10 , 14 , 18 , 19 , 21 , 22 , 26 , 27 , 29 31 , 44 – 47 and 2 studies from mixed population. 15 , 24 Among these included studies, cases were generally recruited in referral centers with documented CAD or stroke, and the controls were without any direct evidence of overt disease.…”
Section: Resultsmentioning
confidence: 99%
“…These 3 polymorphisms were found to occur in frequencies consistent with HWE in the control populations of the vast majority of the published studies. There were 10 studies based on Asian population, 4 , 13 , 16 , 17 , 20 , 23 , 25 , 28 , 32 , 48 16 studies conducted in white population, 10 , 14 , 18 , 19 , 21 , 22 , 26 , 27 , 29 31 , 44 – 47 and 2 studies from mixed population. 15 , 24 Among these included studies, cases were generally recruited in referral centers with documented CAD or stroke, and the controls were without any direct evidence of overt disease.…”
Section: Resultsmentioning
confidence: 99%
“…The genotype of IL-6 is also involved in this process. The IL-6 genotype was significantly associated with thrombosis in children [52] and increased risk of ischemic stroke [53]. …”
Section: Discussionmentioning
confidence: 99%
“…GQ Sun et al [ 28 ] found that the IL-6 rs1800795 G>C polymorphisms presented an increased risk in dominant and recessive models, but they did not find that the IL-6 rs1800796 CC were correlated with an increased risk of coronary artery disease. A study reported that the rs1800796 TT genotype was associated with increased the susceptibility of cerebral thrombosis in the Chinese population [ 29 ]. Previous meta-analysis demonstrated significant association between rs1800796 of IL6 and cancer risk, with the allele G as a risk allele [ 30 ].…”
Section: Discussionmentioning
confidence: 99%